PENGARUH ANGKATAN KERJA, PENDIDIKAN, UPAH MINIMUM, DAN PRODUK DOMESTIK BRUTO TERHADAP PENGANGGURAN DI INDONESIA - Sarito Pasuria (2022)
The phenomenon of employment that often occurs in Indonesia is the high unemployment rate. Unemployment occurs as a result of not optimal absorption of the workforce. The high unemployment rate will have a direct impact on various aspects of life, especially the socio-economic aspects. Therefore, the purpose of this study is to analyze the factors that are thought to have an influence on unemployment, namely the labor force, education, minimum wage, and gross domestic product (GDP) on unemployment in Indonesia in 1990-2020. Multiple linear regression analysis (Ordinary Least Squares/OLS) with time series data from 1990-2020 was used as a data analysis technique in this study. The source of data used refers to secondary data obtained from the Central Statistics Agency. This research is supported by tools in the form of EViews 10 and Microsoft Excel 2019 which are used to test the hypothesis with a significance level of 5% (0.05). Based on the regression estimation results, the research shows that the labor force, education, minimum wage, and gross domestic product have an effect on unemployment in Indonesia simultaneously. On the other hand, partially the labor force, education, and the minimum wage have a significant effect on unemployment in Indonesia, but GDP has no effect on unemployment in Indonesia.